Gender roles in biomass production and management in the Sahel - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2017)
The Sahel is an agriculture-dependent economy facing multiple challenges. Rapid socio-economic change combined with the impacts of climate change, and serious environmental degradation are putting natural resources under increasing stress.